Leadership Style in The Private Sector: Bibliometric Analysis - Akbar Riskal Amani; Syamsul Hadi Senen (West Science Social and Humanities Studies, 2023)
Even though the private sector faces many challenges about human resources, there is still a dearth of literature on HR management methods in the private sector and private enterprise. The purpose of this research is to review the literature on private sector leadership style practices and how they affect other constructs. The Google Scholar database was chosen, and the publish or perish program was utilized to gather literature data. "Leadership style on private sector" is the keyword that is employed. 200 publications from 2018 to 2023 were found in the first search. After that, 43 references were found after the 200 literatures were chosen, Data on the most cited articles, prestigious journals, and top publishers were gathered using the Mendeley reference system and the Publish or Perish program. In addition, the VOS Viewer was used to process the 43 references to provide cluster data, which included the objects that were present in each cluster. There were also illustrations of author networks connected to keywords, overlay visualizations, and density visualizations. An overview of leadership style research is given by this study, with a focus on the commercial sector.